Physiotherapeutic treatment after break and reconstruction of ACL - Adrian Dominiak; Bartłomiej Wrzesiński; Edyta Piechocka; Paweł Wojtczak; Anna Ziółkowska; Wiktoria Śniegowska; Dominika Ciecierska; Marta Bielejewska (Kazimierz Wielki University, 2018)
Injuries of the knee joint are amongst the most common diseases that affect the human body. It is estimated that they affect about 15-30% of all body injuries. Beside the lateral ligaments the most the structure exposed for the any kind of damage is ACL. Concerning the cruciate ligaments, as much as 90% of the injuries are related to ACL [52]. Most often the damage to this structure occurs when practicing sports, both contact (for example basketball, football, martial arts) and non-contact like skiing.